Radiopharmaceuticals for PET Imaging - Issue A - Roivainen, Anne; Li, Xiang-Guo (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Positron emission tomography (PET) is a very useful technique for medical diagnosis and drug development. Radiopharmaceuticals are a key element in PET techniques and one of the pivotal factors influencing the applications of PET. The aim of this Special Issue of Molecules is to report on the recent research work on a number of aspects of PET radiopharmaceuticals and their preclinical and clinical use. More specifically, the content of this Special Issue includes but is not limited to radiolabeling design, radiosynthesis, synthesis techniques, quality control methodologies, GMP production methods, product formulation, in vitro and in vivo preclinical PET evaluations, clinical evaluations, dosimetry, stability study and metabolite analysis, and modeling.